High Performance Single-Molecule Magnets, Orbach or Raman Relaxation Suppression? - Aravena-Ponce, D; Aravena-Ponce, D; Llanos-Silva, L; Llanos-Silva, L (Royal Society of Chemistry, 2020)
The current figure of merit to evaluate Single Molecule Magnet (SMM) performance is the blocking temperature (TB). The best SMMs show TB values close to liquid nitrogen boiling point (77 K) while their Orbach effective demagnetization barriers (Ueff) are significantly larger, exceeding 2000 K in some cases. As current high performance SMMs approach the axial limit, new strategies to suppress demagnetization by vibrational tuning have been suggested. In this article, we analyse a set of 17 current high performance SMMs to identify which demagnetization mechanism is limiting the blocking temperature. For the best systems (TB > 50 K), the limiting mechanism is thermally assisted tunneling and the blocking temperature will depend on the exponential parameters Ueff and τ0. Strategies focusing on Raman (vibrational) suppression are expected to have a limited effect for this group. In contrast, systems with lower blocking temperatures (TB < 50 K) would benefit from such strategies, although they are not expected to surpass current record TB values. The Orbach limit for the blocking temperature can be conveniently estimated using ab initio CASSCF methods. Finally, a recent proposal for a hypothetical high performance SMM is analysed under the presented framework, showing its potential to improve record blocking temperatures. This journal is © the Partner Organisations.